Method for reducing internal resistance of battery and battery with reduced internal resistance
By introducing ferroelectric or thermoelectric materials into lithium-ion batteries and using a spin generator to provide charging current, the problem of large internal resistance of the battery is solved, and the effects of extended battery life, increased capacity and accelerated charging speed are achieved.
Patent Information
- Application Number
- CN202080050535.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-11
- Filing Date
- 2020-07-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-07-10
AI Technical Summary
The internal resistance of existing lithium-ion batteries is large, resulting in short battery life, small capacity and long charging time, and it is difficult to optimize capacity, charging speed and life simultaneously in applications.
The internal resistance of the battery is reduced by introducing ferroelectric or thermoelectric materials into the anode, cathode or other components of the battery and using a spin generator to provide charging current.
A significant reducing the internal resistance of the battery, extending the life of the battery, increasing the battery capacity and charging speed, and can be charged and reused in a shorter time.
Smart Images

Figure CN114207869B_ABST
Abstract
Description
Technical Field
[0001] Various exemplary embodiments relate to devices that store electrical power, such as batteries and accumulators, and corresponding methods of manufacturing such batteries and accumulators. Background Art
[0002] Various batteries have been developed for different uses, and there are a large number of different types, which are mainly derived from the materials used in the anode and / or cathode and / or electrolyte, or from the general technology or structure of the battery, or based on the name of the developer. Common types of batteries include lithium batteries, lithium-ion batteries (LIBs), and polymer-based batteries, just to name a few common types. In addition, electric vehicle development is a rapidly developing branch of industry, and it requires efficient batteries to allow sufficient driving range for vehicle users who have been used to traditional internal combustion engine vehicles. In conjunction with these applications, lithium-based batteries have been discussed as well as nickel metal hybrid (NiMH) and zinc-air batteries.
[0003] If we consider lithium-ion batteries (LIBs) from the general prior art, there are many defects and characteristics that have a negative impact on the lifetime of the battery, on the aging rate of the battery in view of the recharging performed, and on the required battery charging time (from empty / low capacity to full capacity). The main parameters of a battery are its capacity, charging speed and lifetime. Some optimization of these three parameters must be done, otherwise it is impossible to build a LIB with a large capacity, a short charging speed and a long estimated lifetime with the current LIBs of the prior art. At present, some compromises need to be made in these aspects.
[0004] Battery University's web article (see https: / / batteryuniversity.com / learn / article / how_to_prolong_lithium_based_batterics) specifies some general characteristics of batteries and the effects of different parameters on battery life and capacity. For example, the article "BU-808: How to Prolong Lithium-based Batteries" discusses the effects of charging voltage, charging current, depth of discharge (i.e. DoD), state of charge, discharge current, and internal resistance on battery life and capacity. It mentions that if the peak charging voltage exceeds 4.2V / cell, this will greatly shorten the number of discharge cycles, i.e. the life of the battery. Figure 5 of the article BU-808 illustrates this phenomenon well when the charging voltage is 4.25V, 4.30V, and 4.35V. It can be seen that as the charging voltage increases, the capacity increases, but the reduction in the number of cycles is significant.
[0005] Furthermore, article BU-808b and its Figure 4 show the capacity loss caused by structural degradation of old lithium-ion batteries when they are cycled at charge / discharge values of 1, 2 or 3 coulombs (charging voltage of 4.2V and room temperature of 23°C). The higher the charge, the faster the capacity loss will occur, which is related to the number of cycles. The theory is that higher C-rates (i.e. faster charging times) will lead to lithium plating at the anode, which means higher capacity loss.
[0006] Depth of discharge (DoD) is a parameter that describes whether a battery starts charging when its state of charge is partially depleted, or whether the battery has been discharged to a completely empty state of charge when charging starts. The latter case implies 100% DoD, and according to Table 2 of BU-808, this results in a rather short battery life. If a DoD of 60%-80% is applied, the battery life will be significantly increased (even doubled).
[0007] The state of charge (SoC) can be defined as a "bandwidth" where the upper limit defines the charge level from the full (100%) capacity after a charge cycle and the lower limit defines the charge level when charging starts after discharge during battery use. Thus, 100 / 25% means that charging starts when a quarter of the full capacity remains and charging is performed to full capacity. Referring to Figure 6 of article BU-808 (the bottom graph), such a charge / discharge bandwidth results in a large capacity loss (i.e., a shorter service life). At the other end of the range, using a charge / discharge bandwidth of 75 / 65%, the service life is much longer. In practice, this is a partial utilization of the battery. In addition, high voltages and exposure to high temperatures degrade battery performance faster than cycling under normal conditions. It can be inferred from Figure 6 that lithium-ion batteries are quite sensitive to the charge / discharge levels used in practice.
[0008] The discharge current also affects the service life of lithium-ion batteries. For example, a discharge current of 15A causes the capacity to drop by almost 20% after 500 cycles. This is illustrated in Figure 4 of BU-208 ("Cycling Performance").
[0009] The internal resistance of the battery is also a relevant parameter. If the internal resistance of the battery is large, the fast charging process will be prohibited. Ohm's law U = IR means that if R is large, the value of U can easily reach the upper voltage limit of 4.2V, and voltage values above this value are not feasible due to short service life (see above). Because the power P = RI 2 , which means that in the case of a large internal resistance R, the battery will experience a large amount of heat (power loss) energy (power), and in the worst case, the battery may be damaged. The large internal resistance also limits the discharge current. In the case of larger groups of older battery cells in series or parallel, the large internal resistance also makes it difficult to charge them correctly due to the characteristics discussed above.
[0010] The main problem with prior art batteries is that their internal resistance is usually relatively large, and this leads to the secondary problems discussed above regarding short service life, small capacity and long charging time. The secondary problems can be widely seen in practice. In addition, at present, whether it is a good capacity, fast charging speed or long service life of the battery, some compromises must be made, and not all of these can be obtained at the same time, which limits the application field or use scenario of the battery.
[0011] It would therefore be clearly desirable to have a battery, or a group of batteries within a battery, having an internal resistance significantly lower than that of batteries of the prior art. Summary of the invention
[0012] The present invention introduces a method for reducing the internal resistance of a battery. In addition, the present invention includes an aspect of providing a battery with a small internal resistance and a structure of the battery. In one embodiment, this aspect also includes selecting one or more materials within the battery itself. Further aspects include a manufacturing method for a battery and a system for reducing the internal resistance of a battery.
[0013] In other words, the present invention introduces a method for reducing the internal resistance of a battery, characterized in that the method comprises the following steps:
[0014] - providing a charging current to the battery, wherein the charging current comprises spin-polarized and charged electrons,
[0015] - manufacturing a battery such that the battery comprises a ferroelectric or pyroelectric material in the anode, the cathode, another element of the battery or in at least two elements comprised in the battery, wherein after at least one charging cycle of the battery,
[0016] - Obtaining a battery with reduced internal resistance.
[0017] In an embodiment of the present invention, the method further comprises the following steps:
[0018] -Choose the battery to be a lithium polymer (LiPo) battery or a polymer lithium ion battery or a sodium ion battery or a sodium ion polymer battery.
[0019] In an embodiment of the present invention, the method further comprises the following steps:
[0020] - The ferroelectric or pyroelectric material is selected to be polyvinylidene fluoride (PVDF) or a modified material thereof.
[0021] In an embodiment of the present invention, the method further comprises the following steps:
[0022] - Another element of the battery is a solid electrolyte, wherein the battery is a solid-state battery.
[0023] In an embodiment of the present invention, further in the method:
[0024] The ferroelectric or pyroelectric material in the same element or in at least two elements of the cell comprises at least two different materials.
[0025] In an embodiment of the present invention, the method further comprises the following steps:
[0026] -Charging of the battery is performed by a power source via a spin generator, providing a charging current to the battery, wherein the spin generator comprises at least one of PVDF or a modified material thereof, SiC, SiO2, PZT, BiFeO3, BaTiO3, Rochelle salt, zinc oxide, zinc sulfide, aluminum nitride, and bismuth germanate.
[0027] According to a second aspect of the present invention, a battery provided with a reduced or reducible internal resistance is introduced, characterized in that the battery comprises:
[0028] - a ferroelectric or pyroelectric material in the anode, the cathode, another element of the battery or in at least two elements comprised in the battery, wherein after at least one charging cycle of the battery,
[0029] - Obtaining a battery with reduced internal resistance.
[0030] In an embodiment of the present invention, further in the battery:
[0031] The ferroelectric or pyroelectric material in the same element or in at least two elements of the cell comprises at least two different materials.
[0032] In an embodiment of the present invention, the battery is further selected to be a lithium polymer (LiPo) battery or a polymer lithium ion battery or a sodium ion battery or a sodium ion polymer battery.
[0033] In an embodiment of the present invention, in the battery, the ferroelectric or thermoelectric material is selected to be polyvinylidene fluoride (PVDF) or a modified material thereof.
[0034] In an embodiment of the invention, a further element of the battery is a solid electrolyte, wherein the battery is a solid-state battery.
[0035] According to a third aspect of the present invention, a method for manufacturing a battery with reduced internal resistance is introduced. The method comprises the following steps:
[0036] - manufacturing an anode, a cathode or another element of a battery such that the battery comprises a ferroelectric or a thermoelectric material, or at least two elements comprised in the battery comprise a ferroelectric or a thermoelectric material.
[0037] In an embodiment of the invention, the ferroelectric or pyroelectric material in the same element or in at least two elements of the battery comprises at least two different materials.
[0038] In an embodiment of the present invention, the battery is further selected to be a lithium polymer (LiPo) battery or a polymer lithium ion battery or a sodium ion battery or a sodium ion polymer battery.
[0039] In an embodiment of the present invention, the ferroelectric or pyroelectric material is selected to be polyvinylidene fluoride (PVDF) or a modified material thereof.
[0040] In an embodiment of the invention, a further element of the battery is a solid electrolyte, wherein the battery is a solid-state battery.
[0041] According to a fourth aspect of the present invention, a system for reducing the internal resistance of a battery (204, 300) is introduced. The system is characterized in that the system comprises:
[0042] -Battery;
[0043] - Spin generator;
[0044] - power supply; wherein
[0045] - the power source is configured to provide a charging current to the battery via the spin generator, wherein the charging current comprises spin-polarized and charged electrons,
[0046] - the battery is configured to include a ferroelectric or thermoelectric material in the anode, the cathode, another element of the battery or in at least two elements included in the battery, wherein after at least one charging cycle of the battery,
[0047] - Obtaining a battery with reduced internal resistance.
[0048] In an embodiment of the present invention, further in the system:
[0049] The ferroelectric or pyroelectric material in the same element or in at least two elements of the cell comprises at least two different materials.
[0050] In an embodiment of the present invention, further in the system:
[0051] - The battery is further selected to be a lithium polymer (LiPo) battery or a polymer lithium ion battery or a sodium ion battery or a sodium ion polymer battery.
[0052] In an embodiment of the present invention, the ferroelectric or pyroelectric material is selected to be polyvinylidene fluoride (PVDF) or a modified material thereof.
[0053] In an embodiment of the invention, a further element of the battery is a solid electrolyte, wherein the battery is a solid-state battery.
[0054] In an embodiment of the present invention, further in the system:
[0055] -The spin generator includes at least one of PVDF or its modified material, SiC, SiO2, PZT, BiFeO3, BaTiO3, Rochelle salt, zinc oxide, zinc sulfide, aluminum nitride, and bismuth germanate. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 An example of a lithium-ion battery material layer is shown,
[0057] Figure 2 An embodiment of a system for manufacturing a battery having reduced internal resistance is shown.
[0058] Figure 3 An embodiment of a battery having specific element characteristics that allow the effects of the present invention to occur is shown,
[0059] Figure 4a The results of third-party measurements showing the effect of the present invention are shown: battery voltage, charge / discharge current and energy stored in the battery in the test on April 9, 2019,
[0060] Figure 4b The results of third-party measurements showing the effect of the invention are shown: battery voltage, charge / discharge current, and energy stored in the battery in the test on April 8, 2019, and
[0061] Figure 4c A table showing the time to charge the battery to 80% and 100% capacity in the measurements performed. DETAILED DESCRIPTION
[0062] In one embodiment, the present invention introduces a method for reducing the internal resistance of a battery. Similarly, a corresponding battery with a small internal resistance is introduced in the embodiment. In addition, in one embodiment, a system and process for manufacturing a battery with a desired small internal resistance effect are introduced. A method for manufacturing a battery with inventive characteristics is also an aspect of the present invention.
[0063] In one embodiment, the battery used in the present invention is a lithium battery or a lithium ion battery.
[0064] In one embodiment, the battery used in the present invention is a polymer lithium-ion battery.
[0065] In one embodiment, the application battery of the present invention is a sodium-ion battery (ie, sodium ion battery) or a sodium-ion polymer battery.
[0066] Figure 1An example of a lithium-ion battery and its internal material layers is shown. The basic elements (i.e., layers) in such a battery are the cathode, separator (membrane), and anode. Coatings, adhesives, and shell layers may also be applied. In the example shown, the battery structure and dimensions of a Samsung Galaxy Note 7 smartphone are shown, which has a well-known battery problem caused by separation problems between the anode and cathode, resulting in overheating of the battery and even explosive fires and damage to the battery and smartphone. The manufacture and sale of these smartphones has since been cancelled.
[0067] The main parts in this example are Al layer 101 as cathode current collector, cathode layer 102, separator layer 103, anode layer 104, and Cu layer 105 as anode current collector. In this example, their sizes are also shown in the drawings.
[0068] The cathode layer 102 includes a cathode material and a binder, wherein the cathode material may include lithium and other selected metals (labeled as M x ). The anode layer 104 includes an anode material and a binder, wherein the anode material may include graphite or a graphite mixture (marked as C).
[0069] A thinner cathode layer (marked in the figure) can be applied, and particles of 15-30 microns can be applied to the selected metal M in layer 102. In addition, the diaphragm layer 103 can include a diaphragm (for example, 10 microns thick) and a coating made of, for example, aluminum oxide (Al2O3). The aluminum oxide coating can be formed of particles with a size of about 1 micron. The anode layer 104 can include particles with a size of about 10-30 microns. As for the cathode, a thinner anode layer (marked in the figure) can be applied, and optional conductive particles as marked in the figure can be applied.
[0070] As a further illustration regarding the diaphragm layer 103, a coating made of, for example, Al2O3 can be made porous to obtain a large amount of surface area within the diaphragm structure. Although the figures mention micrometer thickness of the coating for the diaphragm layer, porous layers with a thickness of 1-3 micrometers are also feasible.
[0071] Now entering the system according to an embodiment of the present invention, we refer to Figure 2 The system includes a battery and also includes a device configured to convert the battery to a state showing reduced internal resistance. The system may also be referred to as a configuration in which a battery having a specific physical internal structure or material selection can be charged with a dedicated spin generator to produce favorable electrical properties within the battery.
[0072] The main structure of this embodiment is as follows Figure 2 The system includes a main power input (ie, power supply 201 ), an AC / DC converter 202 , a spin generator 203 and a lithium or lithium ion battery 204 .
[0073] Although Figure 2 Reference is made to lithium or lithium ion batteries with dedicated materials, but the invention may also be well applied to sodium ion batteries or sodium ion polymer batteries. In this regard, Figure 2 Only examples are shown.
[0074] The spin generator 203 is configured to perform polarization of the conduction electrons. Polarization actually refers to the spin polarization of the electrons. Although the spin generator 203 itself can be a passive element, the spin generator 203 can have a specific structure that allows this transformation of the conduction electrons. The effect "propagates" to the battery 204, where it also persists for a long time. The demonstration of these effects is discussed later.
[0075] In one embodiment, the spin generator 203 can apply several different methods to produce the so-called spin current. These methods include tunneling methods, i.e. quantum tunneling, so-called "lateral methods", and by using very strong magnetic fields. An example of a device that applies quantum tunneling is a GMR (i.e. giant magnetoresistance) sensor. For example, an example of the lateral method is described in "Control of spin injection by direct current in lateral spin valves" F. Casanova, A. Sharoni, M. E. Rekhinsky, I. Schuller, Physics Department, University of California, CA, USA, 7 March 2009.
[0076] The battery 204 of the system in this embodiment is manufactured so that the battery 204 includes a polarizing material in at least one of the elements including the anode, cathode and / or separator. In addition, the current collector, coating and binder may also be such elements of the battery. In one embodiment, the one or more polarizing materials selected are ferroelectric and / or thermoelectric and / or piezoelectric materials.
[0077] Generally speaking about batteries and their internal components and what the internal resistance of a battery actually includes as components, for batteries without liquid electrolytes, the following can be said. In the case of using solid electrolytes, for the present invention, it has been noted that the solid electrolyte seems to be particularly sensitive to the effects of conductive electrons affected by the spin generator 203. This means that the current affected by the spin generator seems to have a major effect on the solid electrolyte of the battery, which can be regarded as a smaller internal resistance component within the solid electrolyte (e.g., a polymer-based solid electrolyte). The current affected by the spin generator also has the effect of reducing the corresponding internal resistance components of conductive materials (such as anodes and cathodes) and wires leading to / from the electrodes, although this effect currently seems to be much smaller than the internal resistance component formed in the solid electrolyte. In addition, it should be noted that the internal resistance component within the interface between the electrode and the battery chemistry is also relatively large in the overall internal resistance of the battery.
[0078] In one embodiment, two or more different ferroelectric, pyroelectric or piezoelectric materials may be used within the elements of the battery. The main commonality is that the battery includes materials that enable a polarization effect on the current carrying electrons by a charging current from an external power source.
[0079] In an embodiment of the present invention, the battery 204 includes polyvinylidene fluoride (i.e., PVDF) in one or more of the following battery elements: anode, cathode, separator, adhesive, coating, anode current collector, cathode current collector. In one embodiment, PVDF can be used as an adhesive material for the anode, or as an adhesive material for the cathode, or as both an adhesive material for the anode and an adhesive material for the cathode.
[0080] In the embodiments of the present invention, the concept of applying PVDF also includes any modified materials thereof. In other words, the battery can include modified PVDF, wherein the modification can include added functional groups or polymer chains or branches added to the conventional PVDF structure.
[0081] In discussing the manufacturing methods of the battery and the embodiments of the materials used herein, PVDF is a material that is a highly non-reactive thermoplastic fluoropolymer that can be made by polymerization of vinylidene fluoride. The PVDF includes strong piezoelectric properties, where the piezoelectric coefficient of the polarized film can be about 6-7pC / N, which is significantly greater than the piezoelectric coefficient in any other polymer. When polarized, PVDF is a ferroelectric polymer that also has significant piezoelectric and thermoelectric properties.
[0082] In addition, in conjunction with the battery applications and embodiments thereof discussed, a 1-2 wt % PVDF solution dissolved in N-methyl-2-pyrrolidone (NMP) can be mixed with an active lithium storage material (such as graphite, silicon, tin, LiCoO2, LiMn2O4 or LiFePO4) and a conductive additive (such as carbon black or carbon nanofibers). This slurry can be cast onto a metal current collector, and then NMP is evaporated to form a composite electrode or a paste electrode. PVDF can be used because it is chemically inert in the potential range used and does not react with electrolytes or lithium.
[0083] In one embodiment, the PVDF used may be a copolymer or a terpolymer of PVDF, as the first PVDF exploits piezoelectric properties and the latter PVDF exploits ferroelectric properties.
[0084] Figure 3 A simple schematic diagram of the structure of a lithium-ion battery 300 having certain material selections in its elements in an embodiment of the present invention is shown. The cathode current collector 301 can be formed of aluminum, and the anode current collector 306 can be formed of copper. In this example, the separator (303, 304) can be formed of the separator 304 and its coating 303, wherein the material of the coating 303 can be aluminum oxide (Al2O3), but is not limited to only this material. In one embodiment, the cathode material 302 without a binder can be selected from LiNiCoMnO2 (NMC), LiFePO4 (LFP), LiNiCoAlO2 (NCA), LiMn2O4 (LMO), LiNi 0.5 Mn 1.5 O4 (LNMO) and LiCoO2 (LCO).
[0085] The cathode 302 may be formed of a practical cathode material such as cobalt, nickel and / or manganese in a crystalline structure forming a multi-metal oxide material and also with lithium added. The cathode 302 includes a binder, which may be PVDF or other ferroelectric, pyroelectric or piezoelectric material. The manufacturing method of the cathode 302 may be the method described above, but any other feasible manufacturing method may also be applied.
[0086] The same applies to the anode 305, i.e., the anode 305 can be formed of a practical anode material such as carbon black, graphite, graphene, lithium titanate (LTO) or silicon. The anode 305 includes a binder, which can be PVDF or other ferroelectric material, thermoelectric material or piezoelectric material. The manufacturing method of the anode 305 can be the method described above, but any other feasible manufacturing method can also be applied.
[0087] Any modified material of PVDF can be applied to replace PVDF. This involves the corresponding elements of the battery, such as cathode 302, or anode 305, or both cathode 302 and anode 305. In addition, in another embodiment, a solid electrolyte is a possible element to be applied together with PVDF or any modified material thereof.
[0088] The phenomena that appear to occur in a battery according to the invention and in a spin generator according to the invention are explained below.In the following explanation we will use a quantity known as spin torque current.
[0089] Spin torque current is a current that flows between regions with different spin directions of spin-polarized electrons. Spin torque current induces a spin torque on the spin-polarized electrons. Spin torque rotates the spin directions of adjacent regions toward each other. Spin torque current aligns the spins of all spin-polarized electrons in one direction over the entire sample. In contrast to spin current, which is a diffusion of spin accumulation, spin torque current is a diffusion of the direction of spin accumulation.
[0090] In summary, the spins of all spin-polarized electrons across the entire sample try to align in one direction. In the event that the spin direction of the spin-polarized electrons deviates from the common spin direction in a certain region, a spin torque current will flow between different regions of the sample until all spin-polarized electrons realign along a common spin direction. In addition, the spin torque current is only the current of the conduction electrons.
[0091] In other words, the spin torque current is a current that aligns the spin directions between regions with different spin accumulation directions. The spin torque current aligns the spins of adjacent regions in a single direction.
[0092] Some properties of the spin torque current include the following. First, the spin torque current attempts to align the spins of all spin-polarized electrons in one direction across the entire sample. Second, the spin torque current is larger in metals with shorter spin diffusion lengths. Third, the spin torque current is always accompanied by additional spin relaxation. This means that the spin lifetime becomes shorter in the region where the spin torque current flows.
[0093] Still in other words, if the spin directions of the spin-polarized electrons are different in two close regions in a metal, there is mutual diffusion of electrons between the two regions. Since the spin directions of the diffused electrons are different, they induce a spin torque that rotates the spin directions of the spin-polarized electrons. Due to this spin torque, the spin directions of each region are turned toward each other.
[0094] Still to clarify the different concepts (terms) used in the literature, charge current means the flow of electric charges. Spin current means the flow of spins. In relation to the present disclosure, spin torque current means the flow of spin directions.
[0095] In the present invention, when the battery is charged with a dedicated spin generator or other means capable of performing the same effect, the ferroelectric, pyroelectric or piezoelectric material included in the applied battery will be polarized as described above. The charging process will lead to an effect in which the spin directions of each region within the battery (i.e., within and between functional elements) will turn toward each other, resulting in a significant change (i.e., improvement) in the electrical performance of the battery, which is explained in the concluding part of the specification. The spin generator can be generated in various structural ways, and generally in this description, we consider the spin generator to be a "black box", however its function is discussed in detail in this description.
[0096] Now take the existing polymer lithium-ion battery (6745135-10C; 3.7V, 4000mAh) as an example, its manufacturer AAPortable Power Corporation (Richmond, CA, USA) specifies a nominal capacity of 4Ah±5%, a nominal voltage of 3.7V, a standard charge of 0.2C (meaning a standard charging current of 0.8A), a maximum charging current of 4A (corresponding to 1C), a charging cut-off voltage of 4.2V±0.05V, a discharge current of 40A (corresponding to 10C) (the maximum available current is 60A (corresponding to 15C)), and a discharge cut-off voltage of 2.75V. The impedance is specified to be less than or equal to 10mΩ (at 25°C, AC1kHz after charging 50%). The manufacturer has tested the cycle life so that they repeat a certain charge / discharge between the cut-off voltages at a charge / discharge current of 4A until the discharge time remains less than 36 minutes. Then, the battery manufacturer guarantees at least 300 cycles.
[0097] The following durability test was performed on this polymer lithium-ion battery model when the battery was charged with a dedicated spin generator previously proposed in conjunction with the present invention. For practical reasons, this is an AC measurement, so we discuss internal impedance rather than internal resistance. The battery was charged and discharged for 500 (+250) cycles. After 500 cycles, the battery capacity was 95% of the original capacity. The charging cut-off voltage in the test was 4.28V-4.29V. The charging current was 100A (25C) at 0%-95% capacity and 28A (7C) at 95%-100% capacity. The depth of discharge was >100%, and the cut-off voltage was 4.28V and 2.9V. The state of charge (SoC) can vary between 100%-0% (i.e. the entire usable range). The discharge current was 15A on average. Now using these parameters in the durability test, the internal impedance behaves as follows. As a new battery, the internal impedance is 1.38mΩ. During actual use of the battery, the internal impedance is 0.9mΩ-1.0mΩ. After 500 cycles, the internal impedance was 1.8 mΩ. This means that compared to the guaranteed value of 10 mΩ, the internal impedance has dropped by 82%, even after a large number of cycles have been performed in the battery. This is a significant reduction in internal impedance.
[0098] If this battery model were to be used with these durability test parameters, this would age the battery very rapidly when charged with a conventional charging cable, so that the estimated life would only last 10-20 cycles; if the battery were to physically withstand these harsh test conditions, in practice, the battery would last less than a minute because of so much overheating that it would cause an electrical short circuit, resulting in combustion and explosion of the battery.
[0099] Figures 4a to 4c Results of further measurements performed by an external entity (researchers at the University of Eastern Finland in Kuopio) on the same battery model disclosed above are shown. We will describe the experimental setup extensively below.
[0100] In other words, a lithium polymer (LiPo) battery is periodically charged and discharged by using a dedicated spin generator, which exploits the polarization of the conduction electrons. The aim of the test was to show that the battery can be repeatedly charged in a shorter time and with a higher charging current using a dedicated spin generator than by using a conventional charging cable. In the second part of the test, the internal impedance of the battery was measured. The test was carried out on April 9, 2019 at the Department of Applied Physics, University of Eastern Finland.
[0101] The experimental setup used in the battery charging tests consists of the following components:
[0102] -Polymer lithium-ion battery 6745135-10C (AA Portable Power Corp., Richmond, CA, USA), detailed specifications are discussed above
[0103] - MEAN WELL HRP-450-5 switch mode power supply unit (Mean Well Enterprise Co., Ltd., New Taipei City, Taiwan, China)
[0104] -Customized charging control unit (Spindeco Technologies Oy), charging algorithm: two-stage constant voltage control (4.15V / 4.30V)
[0105] - Dedicated spin generator
[0106] -Yokogawa WT500 power analyzer + Yokogawa WT230 power analyzer to verify the readings of the first power analyzer (Yokogawa Electric Corporation, Tokyo, Japan)
[0107] - Thermocouple + DMM for monitoring battery temperature
[0108] - Five H4 bulbs as load during battery discharge
[0109] The battery was charged and discharged periodically so that charging and discharging started automatically. The battery voltage, charge / discharge current and energy stored in the battery were recorded at a rate of 0.2 Hz.
[0110] In the second part of the test, the internal impedance of the LiPo battery is measured according to the IEC 62133 standard. The setup for this measurement consists of the following components:
[0111] -Polymer lithium-ion battery 6745135-10C (AA Portable Power Corp., Richmond, CA, USA), same test battery as above
[0112] -Agilent 33220A 20MHz function / arbitrary waveform generator (Agilent Technologies Inc., Santa Clara, CA, USA)
[0113] - Yamaha Natural Sound Stereo Receiver R-300 (Yamaha Corporation, Hamamatsu, Japan) as an amplifier
[0114] -Digital multimeter for measuring current and voltage
[0115] A function generator provides a sinusoidal signal with a frequency of 1 kHz, and a stereo receiver is used to adjust a current of about 1 A to a series circuit containing a protection resistor and a battery. The voltage across the battery terminals is measured with a digital multimeter, and because the current is 1 A, the measured voltage in millivolts corresponds to the internal impedance of the battery in milliohms.
[0116] The results are Figure 4a and Figure 4b is shown in Figure 4c The presented table is shown.
[0117] Figure 4a The cell voltage, charge / discharge current, and energy stored in the battery are shown for two subsequent charge-discharge cycles tested on April 9, 2019. During the first phase of the charging process, the current exceeded the range of the power analyzer and therefore current data was lost during these periods. Figure 4b A similar graph is shown from a test performed the previous day (April 8, 2019), when the maximum current was slightly lower and the power analyzer recorded the current correctly. It can be seen from the graph that the voltage, current, and energy behaved in the same way in both tests, and therefore the results of the April 9 test (i.e. Figure 4a ) is valid regardless of the partial loss of current data.
[0118] In the second part of the test, the internal impedance of the battery was measured. The voltage across the battery terminals was measured at about 1.3mV at 1A current, which corresponds to an internal impedance of 1.3mΩ.
[0119] therefore, Figure 4a and Figure 4b The two-stage charging process of the battery is clearly shown. In the first stage, the battery is charged to a DC voltage of 4.15V at a current of about 100A in about 80s-90s. In the second stage, the battery is charged to a voltage of 4.3V at a current reduced from about 60A to about 25A in about 120s-130s. Therefore, the total charging time is about 200s-220s. The discharge current is almost constant at about 15A, and the discharge time is about 15min. The maximum energy stored in the battery is about 15Wh.
[0120] Figure 4cThe table in shows more detailed results of the measured charging times for charging the battery to 80% capacity and 100% capacity, respectively. These time values are calculated by assuming that the battery is fully charged when the energy stored in the battery reaches 14.3Wh (the nominal value 13.6Wh + 5% energy loss given by the battery manufacturer). From the results, it can be seen that the battery is charged to 80% capacity in about two minutes and to 100% capacity in just less than three minutes. These results once again verify the consistency of the measurements on April 8 and April 9.
[0121] The measured charging times are much shorter than the known standard charging times for the LiPo battery model used in the tests. This is most likely due to the low internal resistance and the high charging current, both of which also deviate significantly from the known standard values for this battery model. Despite the charging current being well above the standard value, the charge / discharge process was repeatable with good repeatability and the temperature of the battery remained below safety limits (60°C) throughout the test. Extensive durability testing conducted by Spindeco Technologies Oy has shown that LiPo batteries can withstand hundreds of similar charge / discharge cycles without degradation in performance when using a dedicated spin generator. The results of this test are consistent with the observations made during the durability testing.
[0122] Therefore, the impact of a dedicated spin generator on a specific battery structure is significant. The battery life is significantly extended, the battery will withstand harsh charge / discharge conditions, and most importantly, the internal resistance of the battery will remain significantly low (1.8 mΩ) even after 500 charge / discharge cycles. When the internal resistance is kept at a low level, all the problems and drawbacks mentioned in, for example, prior art article BU-808 can be overcome. In embodiments of the present invention, a low level of battery internal resistance is obtained by the proposed dedicated spin generator and the proposed battery structure, as demonstrated in the above-mentioned tests and verified in the above-mentioned third-party measurements ( Figures 4a to 4c ). The advantages of the present invention are therefore substantial and compelling, and have many positive consequences for a variety of application areas.
[0123] Thus, higher charging currents and shorter charging times can be used without degrading the performance of the battery and without any risk of overheating of the battery leading to undesirable consequences (fire / explosion).
[0124] Many application areas benefit from embodiments of the present invention. For example, the automotive industry and especially electric vehicles (i.e. EVs) with their extensive battery cells are good application areas where the proposed embodiments can be used well. Other practical application areas include battery-driven electric working tools and instruments, smart phones and tablets, and even other battery-driven vehicles such as electric bicycles. For example, one application area is formed by batteries that store energy generated by available green energy systems. Examples include wind energy and energy collected via solar panels. Of course, it is also possible to store the generated electrical energy by more traditional systems, where the present invention can be applied.
[0125] One field of application of the batteries of the invention is formed by so-called solid-state batteries. They use solid electrodes and solid electrolytes. The solid electrolyte can be formed of ceramic substances, glass or lithium sulfide, but these are only examples of the invention.
[0126] Of course, any device, gadget, tool, energy storage application, personal and public transport, telecommunication device and virtually any system and equipment using or at least partially applying any type of battery forms a possible field of application for the present invention.
[0127] At least two of the previously mentioned features in this disclosure can be combined to form additional embodiments of the present invention.
[0128] The present invention is not limited to the examples described above, but the scope of the present invention is defined by the claims.
Claims
1. A method for reducing the internal resistance of a battery (204, 300), characterized in that: The method comprises the following steps: - manufacturing a battery (204, 300) such that the battery (204, 300) comprises a ferroelectric or thermoelectric material in at least one of the anode (305), the cathode (302) and the solid electrolyte of the battery (204, 300), - providing a charging current to the battery (204, 300), wherein the charging current comprises spin-polarized and charged electrons, and wherein the charging current polarizes the ferroelectric or thermoelectric material, with all spin-polarized electrons having spins in the same direction, and - obtaining a battery (204, 300) with reduced internal resistance after at least one charging cycle of said battery (204, 300).
2. The method according to claim 1, characterized in that The method further comprises the following steps: - The battery (204, 300) is selected to be a lithium-ion polymer battery or a sodium-ion battery.
3. The method according to claim 1, characterized in that The method further comprises the following steps: - The ferroelectric or pyroelectric material is selected to be polyvinylidene fluoride (PVDF) or a copolymer thereof.
4. The method according to claim 1, characterized in that: Further in the method: - the ferroelectric or thermoelectric material in the battery (204, 300) comprises at least two different ferroelectric or thermoelectric materials.
5. The method according to claim 1, characterized in that The method further comprises the following steps: - The battery (204, 300) is charged by a power source (201) via a spin generator (203), and the charging current is provided to the battery (204, 300), wherein the spin generator (203) comprises at least one of PVDF or its copolymer, SiC, SiO2, PZT, BiFeO3, BaTiO3, Rochelle salt, zinc oxide, zinc sulfide, aluminum nitride, and bismuth germanate.
6. A battery (204, 300) with reduced internal resistance, characterized in that: The battery comprises: - a ferroelectric or thermoelectric material in at least one of the anode (305), cathode (302) and solid electrolyte of the battery (204, 300), and - when a charging current is supplied to the battery (204, 300), wherein the charging current comprises spin-polarized and charged electrons, and wherein the charging current polarizes the ferroelectric or thermoelectric material, the spins of all the spin-polarized electrons are in the same direction, - obtaining a battery (204, 300) with reduced internal resistance after at least one charging cycle of said battery (204, 300).
7. The battery (204, 300) according to claim 6, characterized in that: Further in the battery: - the ferroelectric or thermoelectric material in the battery (204, 300) comprises at least two different ferroelectric or thermoelectric materials.
8. The battery (204, 300) according to claim 6, characterized in that: The battery (204, 300) is further selected to be a lithium-ion polymer battery or a sodium-ion battery.
9. The battery (204, 300) according to claim 6, characterized in that: In the battery (204, 300), the ferroelectric or thermoelectric material is selected to be polyvinylidene fluoride (PVDF) or a copolymer thereof.
10. A system for reducing the internal resistance of a battery (204, 300), characterized in that: The system comprises: - Batteries (204, 300); - Spin generator (203); - a power supply (201); wherein - the battery (204, 300) is configured to include a ferroelectric or thermoelectric material in at least one of the anode (305), cathode (302) and solid electrolyte of the battery (204, 300), - the power source (201) is configured to provide a charging current to the battery (204, 300) via the spin generator (203), wherein the charging current comprises spin-polarized and charged electrons, and wherein the charging current polarizes the ferroelectric or thermoelectric material, with all spin-polarized electrons having spins in the same direction, and - obtaining a battery (204, 300) with reduced internal resistance after at least one charging cycle of said battery (204, 300).
11. The system according to claim 10, characterized in that Further in the system: - the ferroelectric or thermoelectric material in the battery (204, 300) comprises at least two different ferroelectric or thermoelectric materials.
12. The system according to claim 10, characterized in that Further in the system: - The battery (204, 300) is further selected to be a lithium-ion polymer battery or a sodium-ion battery.
13. The system according to claim 10, characterized in that The ferroelectric or pyroelectric material is selected to be polyvinylidene fluoride (PVDF) or a copolymer thereof.
14. The system according to claim 10, characterized in that Further in the system: - The spin generator (203) comprises at least one of PVDF or its copolymer, SiC, SiO2, PZT, BiFeO3, BaTiO3, Rochelle salt, zinc oxide, zinc sulfide, aluminum nitride, and bismuth germanate.
Citation Information
Patent Citations
Self-Charging Powerpack
US20140342192A1
Electrode having an actuating binder
US20170125814A1